2020
DOI: 10.1088/1674-1056/ab7441
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical response of a neuron–astrocyte coupling system under electromagnetic induction and external stimulation*

Abstract: Previous studies have observed that electromagnetic induction can seriously affect the electrophysiological activity of the nervous system. Considering the role of astrocytes in regulating neural firing, we studied a simple neuron–astrocyte coupled system under electromagnetic induction in response to different types of external stimulation. Both the duration and intensity of the external stimulus can induce different modes of electrical activity in this system, and thus the neuronal firing patterns can be sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It has been shown that fluctuations in the membrane potential of neurons can have a significant impact on the distribution of electromagnetic fields, causing changes in magnetic flux and electromagnetic induction across the cell membrane [ 38 , 39 ]. Therefore, it is crucial to consider the effect of electromagnetic induction on neuronal activity in the model.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…It has been shown that fluctuations in the membrane potential of neurons can have a significant impact on the distribution of electromagnetic fields, causing changes in magnetic flux and electromagnetic induction across the cell membrane [ 38 , 39 ]. Therefore, it is crucial to consider the effect of electromagnetic induction on neuronal activity in the model.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the literature, flux-controlled memristors were used in various neuron models to depict the dynamic relation between the membrane potential and magnetic flux [21]. In other words, the flux-controlled memristors were used in the Hodgkin-Huxley neuron model [22][23][24], Izhikevich neuron model [25], FitzHugh-Nagumo neuron model [26], and threedimensional (3D) [27][28][29][30][31]/two dimensional (2D) [32][33][34] Hindmarsh-Rose neuron model to depict the electromagnetic induction effect. These memristive neuron models can generate abundant firing patterns since the involvement of the flux-controlled memristor.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] That is to say, the neuron can realize its functions by feeling externally applied stimulus and conduc-tion excitation of the change electrophysiology. [17,18] To date, many explorations have revealed that externally applied stimulus and electromagnetic induction influence the dynamical properties of neuron electrical activities. By introducing an external applied current into HR model, various types of coexisting asymmetric bursters were disclosed.…”
Section: Introductionmentioning
confidence: 99%